2004
DOI: 10.1074/jbc.m406320200
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase 7 Associates with Hypoxia-inducible Factor 1α and Increases Transcriptional Activity

Abstract: Hypoxia-inducible factor (HIF)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
160
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(168 citation statements)
references
References 41 publications
4
160
1
3
Order By: Relevance
“…HDAC-7 -/-mouse embryos display defects in the development and integrity of blood vessels (38). Moreover, HDAC-7 protein has been implicated in several biologic processes, including regulation of gene expression, either as coactivator or corepressor (39,40), and it plays a role in T cell differentiation by inducing Nur-related protein 77 (35).…”
Section: Discussionmentioning
confidence: 99%
“…HDAC-7 -/-mouse embryos display defects in the development and integrity of blood vessels (38). Moreover, HDAC-7 protein has been implicated in several biologic processes, including regulation of gene expression, either as coactivator or corepressor (39,40), and it plays a role in T cell differentiation by inducing Nur-related protein 77 (35).…”
Section: Discussionmentioning
confidence: 99%
“…This repression occurs due to the targeting of HIF-1a/p300 complex by HDACi. HDACi could also decrease HIF-1a activation by inhibiting HDAC7 activity, since under hypoxic conditions, HDAC7 translocates to the nucleus, where it can interact with HIF-1a and increase its transcriptional activity (Kato et al, 2004).…”
Section: Hdaci Inhibits Angiogenesismentioning
confidence: 99%
“…Heat shock stimulation induced HDAC4 nuclear translocation (Dai et al, 2005), hypoxic conditions, in the presence of HIF-1a, drive HDAC7 to the nucleus (Kato et al, 2004) and hormone occupancy of the AR induces nuclear transfer of HDAC7 and -4 (Halkidou et al, 2004;Karvonen et al, 2006). The mechanism by which these signals lead to class IIa HDACs nuclear accumulation is not known and undoubtedly deserves further investigation.…”
Section: Signalingmentioning
confidence: 99%
“…Supporting this in the case of class IIa HDACs, the C terminus of HDAC4 and -7 but not HDAC5 has been shown to bind to hypoxia-inducible factor 1a (HIF-1a), a transcription factor that controls expression of genes responsive to low oxygen tension. Surprisingly, association with HDAC7 leads to increased HIF-1a transcriptional activity under hypoxic conditions (Kato et al, 2004). The exact mechanism underlying the transcriptional activation of HIF-1a by some members of class IIa HDACs remained unclear until recently, when it was reported that inhibition of HDAC4 by small interfering RNA had a positive effect on HIF-1a acetylation, which correlated with reduced stability (Qian et al, 2006).…”
Section: Atypical Rolesmentioning
confidence: 99%